MiR-202-3p determines embryo viability during mid-blastula transition - Hu, Ruiqin; Xu, Yanna; Han, Bingshe; Chen, Yi; Li, Wenhao; Guan, Guijun; Hu, Peng; Zhou, Yan; Xu, Qianghua; Chen, Liangbiao (Frontiers in Cell and Developmental Biology, 2022)
Developmental growth is an intricate process involving the coordinated regulation of the expression of various genes, and microRNAs (miRNAs) play crucial roles in diverse processes throughout animal development. The mid-blastula transition (MBT) is a developmental milestone when maternal RNAs are cleared and the zygotic genome programmed asynchronous cell division begins to drive embryogenesis. While mechanisms underlying MBT have been intensively revealed, factors regulating cell proliferation at the transition remain largely unknown. We report here a microRNA, miR-202-3p to be a key factor that determines embryonic fate during MBT in zebrafish. A miR-202-3p antagomir specifically terminated embryo development at the mid-blastula stage. In vivo deletion of the miR-202 locus recapitulated the fatal phenotypes, which were rescued only by miR-202-3p or its precursor. Transcriptome comparison revealed >250 RNAs including both maternal and zygotic origins were dysregulated at MBT in the miR-202−/− embryos, corresponding with arrays of homeostatic disorders leading to massive apoptosis. A trio of genes: nfkbiaa, perp and mgll, known to be intimately involved with cell proliferation and survival, were identified as direct targets of miR-202-3p. Importantly, over- or under-expression of any of the trio led to developmental delay or termination at the blastula or gastrula stages. Furthermore, nfkbiaa and perp were shown to inter-regulate each other. Thus, miR-202-3p mediates a regulatory network whose components interact closely during MBT to determine embryonic viability and development.